Regain balance: Recovery of postural perturbations of people with and without chronic low back pain - Martin Götze; Markus Koch; Reinhard Blickhan (International Journal of Spine Research - Peertechz Publications, 2019)
Background: Chronic low back pain (CLBP) seems to influence adjustment of posture. The application of external disturbances is used to gain a better understanding of movement strategies and their possible alterations to restore postural balance in people with CLBP. Objective: This cross-sectional observational study aimed to investigate the kinematic quality of postural recovery to sudden lateral perturbations between people with and without CLBP. Methods: Three types of perturbations at two amplitudes applied over a hand held grip were used to test adaptive postural control in an upright standing position. For analyzing the kinematic quality of postural recovery, the range of motion, the time to regain balance and the number of postural adjustments of the shoulder- and pelvis angle were examined. Results: People with CLBP needed reduced time for stabilization and reduced number of adjustments of the pelvis angle. These findings are linked to a specific character of applied perturbations. No differences were found for the range of motion between the two groups.  Conclusion: Among the different offered types of disturbances, the sudden loading perturbations that could cause a possible buckling of the spinal column, led to a limited movement response of the people with CLBP. It seems that this reaction depends on the level of loading which activates stress induced adjustments.